Genomic regions harboring insecticide resistance-associated Cyp genes are enriched by transposable element fragments carrying putative transcription factor binding sites in two sibling Drosophila species - Carareto, Claudia M. A. [UNESP]; Hernandez, Eric H. [UNESP]; Vieira, Cristina (Elsevier B.V., 2014)
In the present study, an in silico analysis was performed to identify transposable element (TE) fragments inserted in Cyps with functions associated with resistance to insecticides and developmental regulation as well as in neighboring genes in two sibling species, Drosophila melanogaster and Drosophila simulans. The Cyps associated with insecticide resistance and their neighboring non-Cyp genes have accumulated a greater number of TE fragments than the other Cyps or a random sample of genes, predominantly in the 5'-flanking regions. Most of the insertions were due to DNA transposons, with DNAREP1 fragments being the most common. These fragments carry putative binding sites for transcription factors, which reinforces the hypothesis that DNAREP1 may influence gene regulation and play a role in the adaptation of the Drosophila species. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cytochrome P450 monooxygenases; Transposable elements; DNAREP1; TFBS; Gene expression regulation